Analisis Sentimen Ulasan Perbedaan Aplikasi BCA Mobile dengan MYBCA di Playstore Menggunakan Metode Lexicon - Yoman, Jesslyn Patricia; Cok, Cherry; Laigusten, Kerstyn; Zovintho, Geovani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aimed to analyze and compare user sentiment toward two digital banking applications owned by Bank Central Asia: BCA Mobile and myBCA, based on user reviews collected from the Google Playstore. The research employed a text-based quantitative approach, using a lexicon-based sentiment analysis method to classify user opinions into positive, negative, and neutral categories. Data were collected through web scraping and processed using text preprocessing techniques such as tokenization, stopword removal, and stemming. The results showed that most reviews were neutral, with myBCA receiving a higher proportion of positive reviews than BCA Mobile. Visual analyses through charts and wordclouds successfully illustrated differences in user perception related to application features such as login convenience, user interface design, and technical issues. This study concluded that sentiment analysis is an effective tool to evaluate user experience and provide strategic insights for the future development of digital banking services.